Fighting RNA viruses with a gold nanoparticle Cas13d gene-editing armor - Alessandro De Carli; Domenico Favaro; Carolina Filipponi; Fabio Filippini; Rossella Fonnesu; Erika Plicanti; Silvia Nottoli; Piotr Barski; Agnieszka Lindstaedt; Dariusz Witt; Alessandra Falleni; Giada Frenzilli; et al. (Molecular Therapy: Nucleic Acids)
A novel Cas13d-based gene-editing approach has been developed to target viral RNAs in infected cells, reducing the replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Zika virus (ZIKV) by up to 90% compared with controls. Despite its potential, the use of Cas13d as an antiviral faces several challenges that limit its effectiveness before reaching target cells. This study presents a proof-of-concept strategy for constructing Cas13d with gold nanoparticles (Au_NPs) to destroy SARS-CoV-2 and ZIKV genomes into cells. The Au_NPs Cas13d complexes were administered to Huh-7 cells infected with either virus, in single or multiple doses. The study demonstrated that Au_NPs Cas13d cuts target RNAs with comparable efficiency as lipofected ribonucleoprotein (RNP). Additionally, we found that Au_NPs Cas13d can spontaneously enter cells by endocytosis or diffusion, before the first 4 h of treatment. Au_NPs Cas13d co-localized with SARS-CoV-2 virions in early endosomes and reduced SARS-CoV-2 replication after a single administration, unlike RNPs, which showed no antiviral activity. However, Au_NPs Cas13d was less efficient at reducing ZIKV replication compared with lipofected Cas13d-RNPs, likely due to different intracellular localization. These results suggest that Au_NPs can be adapted as a new antiviral strategy, highlighting an innovative delivery method of Cas13d against viruses without the need for transfecting, providing a new gene-editing-based approach against emerging RNA viruses.